Вплив загроз функціональних складових на рівень економічної безпеки підприємств (на прикладі підприємств автомобільного транспорту) - Нікітіна, Аліна Вадимівна; Горовий, Дмитро Анатолійович (Сумський державний університет, 2017)
У статті проаналізовано концепції визначення сутності економічної безпеки підприємства. Визначено головні функціональні складові економічної безпеки підприємства. Обґрунтовано, що факторне оточення суттєво впливає на рівень економічної безпеки підприємства (на прикладі автотранспортних підприємств). Доведено, що деструктивні явища (загрози), які були інтерпретовані як ті, що відбиваються на рівні певної складової економічної безпеки підприємства (фінансової, кадрової, техніко-технологічної, інвестиційно-інноваційної, політико-правової, інформаційної, екологічної), здійснюють вплив не тільки на загальний рівень економічної безпеки, але й на інші функціональні складові. Проаналізовано найсуттєвіші загрози, які можуть спричинити негативні тенденції та порушення у роботі підприємств автомобільного транспорту. Обґрунтовано необхідність подальшого, більш глибинного дослідження впливу таких деструктивних та дестабілізуючих явищ, що можуть викликати непоправимі наслідки та взагалі загрожувати функціонуванню підприємства.

The concepts of determining the essence of economic security of a company is analyzed in the article. The main functional components of the economic security of a company are determined. It is substantiated that the environment factor significantly affects the level of economic security of the company (by the example of motor transport enterprises). It is proved that the destructive phenomena (threats) are reflected at the level of a certain component of the economic security of a company (i.e. financial, personnel, technical and technological, investment-innovation, political, legal, information, environmental). Also they reflect on the general level of economic security. It is concluded that the approaches to understanding the category of economic security of a company are different after having investigated and summarized the fundamental works of domestic and foreign scientists. The absence of a single universal thought to the interpretation of the essence and economic content of this concept causes the need for its further more detailed research that would reveal the natural connections and relations in modern economic realities. Taking into account the complexity, ambiguity, unpredictability and heterogeneity of destructive and destabilizing phenomena that affect the level of economic security, it is proposed to highlight the effects of threats in the context of all functional components. The aim is to identify the cause-effect relationships between threats and indicators that are used to assess the level of economic security by the example of motor transport enterprises. The main purpose of this article is to identify the essential characteristics of the economic security of the enterprise, to analyze the factor environment of economic security and its influence through the prism of the functional components of economic security by the example of motor transport enterprises. The simulation model of the influence and interrelation of threats, indicators of the economic security of motor transport enterprises is proved with the purpose of comprehensive disclosure the essence of the multifaceted process of economic security management of the motor transport enterprises. It serves as an important theoretical basis for developing a program of actions for a company aimed at ensuring a stable operation, independence and autonomy in the current and future periods. Analyzing the impact of information component threats on indicators of other functional components of the economic security of motor transport enterprises and understanding the information dependence of modern business entities, we come to the conclusion that threats of inefficient communications between departments, insufficient financing of information services, low level of objectivity of external and internal information is an important disincentive to effective development and the work of motor transport enterprises. Threatening the innovation and investment component of the economic security of motor transport enterprises, destabilizing and destructive phenomena also violate the normal functioning of financial, technical, technological, environmental, political and legal functional components. Thus, the provided analysis of the potentially possible effects of destructive and destabilizing phenomena indicates the need to solve the problem of leveling the impact of threats by the level of economic security of motor transport enterprises. The next stage of the study would be a comprehensive assessment of such destructive and destabilizing phenomena impact that can cause irreparable consequences and in general threaten the functioning of the enterprise.
The influence of functional components threats on the level of economic security of companies (by the example of motor transport enterprises)
Keywords: економічна безпека підприємства; внутрішнє середовище; зовнішнє середовище; ризики економічні; economic security of a company; internal environment; external environment